Internationalization of SMEs in Malaysia! Manager perception and expectation / Noorasmareena Che Ab Latif and Nur Mohammad Royza Alif Zahuri - Che Ab Latif, Noorasmareena; Alif Zahuri, Nur Mohammad Royza (Faculty of Business and Management, 2013)
In Malaysia business trend today, many Small and Medium Enterprise (SME) company seek the opportunity to expand their business to international level. However, there are several factors that influence the internationalization of SMEs in Malaysia. Thus, a study is carried out to see the matters at hand. The title of this research paper is “Internationalization of SMEs in Malaysia! Manager Perception and Expectation”. The purpose of this research is to see the relationship between independent variables which are Financial, Technology and Human Capital toward dependent variable which is internationalization of SMEs in Malaysia. The objective highlight in this research are to know the most influencing factors of SMEs to internationalize, the current SMEs export contribution and at the same time to test the relationship between financial, technology and human capital with internationalization of SMEs in Malaysia. In gathering the data, 50 set of questionnaires was distributed to managers of 50 SMEs company around Malaysia that was choose randomly by the researchers. In this research, it is found that two independence variables which are technology and human capital are significant with the dependent variable which is internationalization of SMEs in Malaysia. The most dominant factor or the most significant variable among all the independent variables is the technology.